EVALUATION OF PRE-FRACTIONATION COLUMN OPERATION CONTROL CONFIGURATION IN CRUDE OIL DISTILLATION SYSTEM - Chandra, Jonathan
The fuel demand for Indonesia in 2018 (including biodiesel) has reached 465.7 million barrels. Since the production of fuel from domestic refineries is around 278.1 million barrels, it is necessary to import 187.6 million barrels and the fact that followed by the tendencies of increasing energy demand each following year. In meeting these needs, upgrading operation capacity is required by adding pre-flash units to the existing oil refinery unit. This capacity upgrade is quite effective in meeting energy needs at a relatively short period of time and relatively low investment, so that it becomes the best choice in solving the problem. The ASPEN HYSYS simulation of old unit results in comparison with field results for old units shows very close results. While also operating within hydraulic, heat transfer and mechanical conditions operating range. These results can then be developed to add pre-flash units followed by operation modifications to be carried out in revamp to create a new simulation unit. The simulation of new unit results operates within the range of equipment limitations, achieve product specifications, and within the specified product quantity limits. The simulation results of the new unit were then modified so that it could be isolated for the pre-flash unit which was developed into a dynamic model including the addition of process control. The dynamic pre-flash unit simulation that has obtained steady results is compared to the steady results of the new unit pre-flash simulation. The results obtained show that qualitatively, quantitatively, and operating conditions are relatively similar. The method use for control tuning is Ziegler-Nichol because from various methods, it shows the lowest Integral of Absolute Error (IAE) value. Various operational changes to the pre-flash unit were made to explore the impact of the changes and the controls were able to remain responsive in responding to changes when activated.